PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA SMP NEGERI 1 CIDAHU DENGAN MENERAPKAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) - Lia Yulianah; Ricki Yuliardi; Zuli Nuraeni (Program Studi Pendidikan Matematika STKIP Muhammadiyah Kuningan, 2016)
This research having target to know ability of understanding concept mathematics student by applying model study of co-operative type NHT with student obtaining conventional study. Method which used in this research that is experiment method by using non-equivalent control group design. This research entangle experiment class and control class of class VII in SMPN 1 Cidahu of school year 2015/2016. This Research use instrument of essay test to know ability of understanding concept mathematics student and also use enquette respon student to know student respon to applied study. Pursuant to result of research that ability of understanding concept mathematics of student using model study of NHT more better than student obtaining conventional study. As for enlargement to ability understanding concept mathematics of student experiment class with mean 0,31 residing in medium category. Besides from result of enquette of respon student equal to 95,12% show positive respon of student to applied study.